2007
DOI: 10.1299/jee.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Laser Mass Spectrometry: Rapid Analysis of Polychlorinated Biphenyls in Exhaust Gas of Disposal Plants

Abstract: Effective prevention from the leakage of Polychlorinated Biphenyls (PCBs) requires the rapid analysis with on-line detection, but conventional methods require extensive analytical time (several days per sample) and are thus unsuitable. The objective of the research reported here was to develop the Laser Ionization / Ion Trap Storage / Time of Flight Mass Spectrometry (LI-IT-TOFMS) capable of monitoring PCBs within 1 min/sample, as applied to exhaust gas and the atmosphere of the disposal work environment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…45), 46) We used the internal standard gas (2,4-di-chlorinated toluene) in order to check the correct operation of the monitoring system. 46) It was confirmed that the PCB concentration in the environmental gas (which is substantially lower than the value of 0.10 mg/m 3 N as specified by statutory regulations), can be analyzed within 1 min.…”
Section: )῏68)mentioning
confidence: 99%
See 1 more Smart Citation
“…45), 46) We used the internal standard gas (2,4-di-chlorinated toluene) in order to check the correct operation of the monitoring system. 46) It was confirmed that the PCB concentration in the environmental gas (which is substantially lower than the value of 0.10 mg/m 3 N as specified by statutory regulations), can be analyzed within 1 min.…”
Section: )῏68)mentioning
confidence: 99%
“…4.4.2 Applicability of the exhaust gas and the atmosphere of the work environment 45) In the exhaust gas of the hydrothermal decomposition processes and the workplace atmosphere, the main components were N 2 , CO 2 , O 2 , and H 2 O and air. These gases were contaminated by several trace components attributed to insulating oils, cleaning chemicals, and their decomposition products to the order of mg/m 3 N. The concentrations of these trace components were dependent on the plant operating conditions and varied by several orders of magnitude.…”
Section: )mentioning
confidence: 99%
“…The detection limit of measured species using TOFMS is often ppb or less. TOFMS with several ionization processes has been applied to measure hydrocarbons and nanoparticle constituents at low concentration ranges of ppb–ppt [ 46 , 47 , 48 , 49 , 50 ], as well as waste disposal and treatment plants [ 51 , 52 , 53 ]. There are other developed TOFMS applications in several fields, such as the medical and pharmaceutical fields [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…TOFMS has been applied to measure hydrocarbons and nanoparticle constituents with low concentration range of ppb-ppt, [25][26][27][28][29] as well as waste disposal and treatment plant. [30,31] Considering the features of TOFMS, the combined method of laser breakdown and TOFMS becomes an attractive tool for trace elemental composition measurement. [29] In this method, the laser is introduced to break and ionize the measured species with detection of atomic ion signals using TOFMS.…”
Section: Introductionmentioning
confidence: 99%